Козлы!: роман : пер. с фр. [Ольги Лемпицкой] / А. Бюто - Бюто Ариэль (Легкие книги, 2007)
Экземпляры: аб. (20151106) / Инвентарный номер: 56796 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Б 98 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44